2002
DOI: 10.1002/app.11318
|View full text |Cite
|
Sign up to set email alerts
|

Human serum albumin (HSA) adsorption with chitosan microspheres

Abstract: ABSTRACT:In this study, chitosan microspheres were prepared and characterized for adsorption of human serum albumin (HSA) as affinity sorbent. The chitosan microspheres were obtained with a "suspension crosslinking technique" in the size range of 30 -700 m by using a crosslinker, i.e., glutaraldehyde. The chitosan microspheres used in HSA adsorption studies were having the average size of 170 Ϯ 81 m. Adsorption medium pH and the initial HSA concentration in the adsorption medium were changed as 4.0 -7.0 and 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…In this section we study the correlation between the morphology and the bioimmobilization performance of chitosan. The data in Tables 1 and 2 show that immobilized cellulase using the two types of support evidently demonstrate good results, and the amount of cellulase bound to the support is fairly high (17–150 mg g −1 ) compared with literature values (3–50 mg g −1 ) 20–23. It is revealed that chitosan with smaller pore or particle size possesses more entrances to entrap enzyme than conventional chitosan support with large pore or particle sizes ( ca 500–300 µm), which leads to much improved bioimmobilization ability.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…In this section we study the correlation between the morphology and the bioimmobilization performance of chitosan. The data in Tables 1 and 2 show that immobilized cellulase using the two types of support evidently demonstrate good results, and the amount of cellulase bound to the support is fairly high (17–150 mg g −1 ) compared with literature values (3–50 mg g −1 ) 20–23. It is revealed that chitosan with smaller pore or particle size possesses more entrances to entrap enzyme than conventional chitosan support with large pore or particle sizes ( ca 500–300 µm), which leads to much improved bioimmobilization ability.…”
Section: Resultsmentioning
confidence: 76%
“…However, the immobilization behavior (bound capacity) of chitosan may vary significantly according to different methods. Furthermore, considering the large particle size ( ca 500–300 µm) of conventional chitosans,19, 20 their specific capacity for protein still remains poor (<50 mg g −1 support)20, 21 and, moreover, the activity of immobilized cellulase is fairly low 22, 23…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, silica has much higher mechanical stability than agarose but is unstable against alkaline solution [11]. Therefore, investigators are still trying to develop novel chromatographic support materials and chitosan is one of them [12].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the molding, investigation and application of chitosan have been restricted. The methods for producing porous and spherical chitosan microbeads, such as the "suspension evaporation method" [6] and the "suspension crosslinking technique" [9,21] using chitosan acid aqueous solutions, have been reported. These methods require the use of organic solvents and emulsifier.…”
Section: )-N-acetyl-d-glycanmentioning
confidence: 99%
“…Chitosan and derivatives have become useful polysaccharides in the biomedical field. Especially, these microparticles have been utilized as chromatographic packings [5,6], enzyme-immobilized support [7,8], affinity adsorbents for proteins [9], endotoxin adsorbents [10] and drug carriers [11,12]. Generally, it was popular to use chitosan as antibacterial compounds in agriculture, as elicitors of plant defense responses [13], as additives in the food industry, as flocculating agents for wastewater [14] and as pharmaceutical agents in biomedicine [15,16].…”
Section: Introductionmentioning
confidence: 99%